Phase evolutions and electrical properties in BaTiO3-BaFe 0.5Nb0.5O3 ceramics - Intatha U. (2014)
In this work, BaFe0.5Nb0.5O3 (BFN) was added to BaTiO3 (BT) to form the solid solution. The investigation of phase evolution, physical properties and electrical properties of the binary system (l-x)BT-xBFN where x = 0, 0.2, 0.4 and 0.6 was carried out. The BT and BFN powders were prepared separately using a calcination technique with optimum calcinations temperature for producing both BT and BFN powders. XRD results revealed that the BT-BFN ceramics with BFN content of x less than 0.4 contain the ferroelectric tetragonal perovskite phase whereas the composition with BFN content of x = 0.6 changes symmety to the cubic phase. From the evidences including phases, microstructures and ferroelectric and dielectric data of the BT-BFN ceramics, it is inferred that the morphotropic phase boundary occurs around the composition ox = 0.4. © 2009 American Institute of Physics.